HUBUNGAN INTENSITAS MEMBACA DENGAN KETERAMPILAN MENULIS KARANGAN NARASI SISWA KELAS V SEKOLAH DASAR - Wewen Wewen; Heru Susanto; Evinna Cinda Hendriana (PEDAGOGIKA: Jurnal Pedagogik dan Dinamika Pendidikan, 2023)
Reading and writing are very important skills in education. Indonesia is ranked 62nd out of 70 countries, or is in the bottom 10 countries that have a low literacy rate. This study aims to determine how big the relationship between reading intensity and narrative essay writing skills of elementary school students. The method used is correlation research with a quantitative approach. The population in this study were all fifth grade elementary school students. The sampling technique uses saturated samples, where all members of the population are used as research samples. The data collection techniques in this study used indirect communication techniques and measurement techniques, namely using a reading intensity questionnaire and a narrative essay writing skills test. The data analysis technique used is the Pearson Product Moment Correlation. The results showed that there was a significant correlation (correlation) between reading intensity and narrative essay writing skills. With a correlation coefficient of 0.6419 (classified as high), which means that reading intensity plays a very important role in influencing narrative essay writing skills with a contribution of 41.21%. From the results of the research that has been done, there is a relationship between students' reading intensity and narrative essay writing skills.